Frequency Control of Distributed Energy Resources in Distribution Networks⁎. Issue 28 (2018) - Ortega, Álvaro; Milano, Federico
Abstract: This paper studies the contribution of distributed energy resources (DERs) installed in distribution systems to the frequency regulation of transmission systems. To this aim, the paper compares three strategies to retrieve the input signal of the DER frequency regulators, namely (i) measuring the frequency at the point of common coupling with the transmission system; (ii) measuring locally the frequency signals at every bus with regulation of the distribution system; and (iii) computing the average of such signals. The impact of measurement issues caused by the computation of the numerical derivative of the bus voltage phase angle, as well as of noise, delays and loss of information are also thoroughly analyzed in the case study.